Recurrent Electrical Storm in a Patient with Chronic Heart Disease: A Case Report - Grabski, Wojciech; Strzałkowska, Paulina; Hobot, Maciej; Szaj, Dominika; Raczkowska, Michalina; Trojańska, Aleksandra (Quality in Sport, 2025)
Background: Electrical storm (ES) is a life‑threatening cardiac emergency characterized by recurrent, sustained ventricular tachycardia (VT) or ventricular fibrillation (VF) episodes that are often refractory to standard therapies. It predominantly affects patients with structural heart disease - most notably those with ischemic cardiomyopathy and chronic heart failure with reduced ejection fraction (HFrEF). Case Presentation: We describe a 75‑year‑old man with ischemic cardiomyopathy and HFrEF admitted for sustained VT unresponsive to conventional management. His history included multiple catheter ablations, prior myocardial infarction, and an implanted ICD placed for recurrent ventricular arrhythmias. Despite additional ablations and antiarrhythmic medication, he continued to experience electrical storms. Definitive rhythm control was achieved via a multidisciplinary strategy comprising left stellate ganglion block, upgrade to cardiac resynchronization therapy‑defibrillator (CRT‑D), personalized ICD reprogramming, and initiation of flecainide in combination with propranolol. Device interrogation at follow‑up confirmed effective biventricular pacing and complete suppression of sustained ventricular arrhythmias. Conclusion: This case underscores the complexity of managing ES in patients with advanced structural heart disease and multiple comorbidities. Individualized device programming, innovative pharmacological regimens, and targeted interventional techniques can stabilize patients refractory to standard approaches. A holistic, team‑based model of care is essential to optimize outcomes and improve quality of life in this high‑risk population.